ENVIRONMENTAL PROTECTION POST ESTABLISHMENT OF OMNIBUS LAW ON JOB CREATION IN THE PERSECTIVE OF LOCAL GOVERNMENT AUTHORITY - Malicia Evendia; Ade Arif Firmansyah (Progressive Law Review, 2023)
The dynamics of regulation of environmental protection, with the publication of the Omnibus Law on Job Creation, has had an impact on the content contained in Law Number 32 of 2009 concerning Environmental Protection and Management. The existence of the Omnibus Law on Job Creation has changed at least 27 articles, added 4 articles, and 10 articles were deleted in Law Number 32 of 2009. This paper aims to reflect on the legal implications of environmental protection after the Omnibus Law on Job Creation on regional authorities. The results of the study show that the Omnibus Law on Job Creation has reduced the authority of local governments in protecting the environment. There have been several withdrawals of local government affairs to the central government (recentralization), as well as the strengthening of evaluation instruments by the central government. This legal implication can be a challenge and a threat to solving problems and protecting the environment in the region. On the other hand, this can reduce the spirit of environmental decentralization and weaken the spirit of regional autonomy.